Bagaimana Literasi Keuangan Mempengaruhi Perilaku Pengelolaan Keuangan Pribadi Mahasiswa Pendidikan Ekonomi ? - Rifdani Rifdani; Efni Cerya (Universitas Negeri Padang, 2022)
The purpose of this study was to determine how financial literacy affects the personal financial management behavior of Economic Education students, Padang State University. The type of research used is causative research with a population of all students of Economics Education, Faculty of Economics, Padang State University or as many as 464 people. And the technique used in sampling is purposive random sampling with a total sample of 82 students of Economics Education. Data collection techniques are carried out by distributing questionnaires or online questionnaires. To ensure that the questionnaire or questionnaire used in this study was used to test the validity and test reliability. Before performing the data analysis technique, the classical assumption test was carried out using the normality test, multicollinearity test and heteroscedasticity test. The data analysis technique used is simple regression analysis with the help of SPSS 21. The results of this study indicate that financial literacy has a significant effect on the personal financial management behavior of Economic Education students. Keywords : literacy, personal financial management behavior